Application of magnetic resonance spectroscopy in the differentiation of high-grade brain neoplasm and inflammatory brain lesions Aplicação da espectroscopia por ressonância magnética na diferenciação de lesões expansivas encefálicas neoplásicas e inflamatórias - José Roberto Lopes Ferraz-Filho; Pedro Vieira Santana-Netto; Jose Alves Rocha-Filho; Aline Sgnolf; Fernando Mauad; Rafael Angelo Sanches (Arquivos de Neuro-Psiquiatria)
This study aims at evaluating the application of magnetic resonance spectroscopy (MRS) in the differential diagnosis of brain tumors and inflammatory brain lesions. The examinations of 81 individuals, who performed brain MRS and were retrospectively analyzed. The patients with ages between 10 and 80 years old, were divided into two groups. Group A consisted of 42 individuals with diagnoses of cerebral toxoplasmosis and Group B was formed of 39 individuals with diagnosis of glial neoplasms. On analyzing the ROC curve, the discriminatory boundary for the Cho/Cr ratio between inflammatory lesions and tumors was 1.97 and for the NAA/Cr ratio it was 1.12. RMS is an important method useful in the distinction of inflammatory brain lesions and high-degree tumors when the Cho/Cr ratio is greater than 1.97 and the NAA/Cr ratio is less than 1.12. And so this method is important in the planning of treatment and monitoring of the therapeutic efficiency. O presente estudo tem como objetivo avaliar a aplicação da espectroscopia por ressonância magnética (ERM) no diagnóstico diferencial entre lesões expansivas encefálicas inflamatórias e neoplásicas. Foram analisados retrospectivamente 81 indivíduos que realizaram exames de ERM com idade entre 10 a 18 anos, divididos em dois grupos. O grupo A foi formado por 42 indivíduos com diagnóstico de neurotoxoplasmose e o grupo B foi formado por 39 indivíduos com diagnóstico de neoplasias gliais. Após análise da curva ROC observou-se que o valor discriminatório da relação Co/Cr entre lesões inflamatórias e neoplásicas foi de 1,97 e da relação Naa/Cr foi de 1,12. A espectroscopia por RM é um método útil na distinção de lesões expansivas inflamatórias e neoplasias de alto grau quando a relação Co/Cr é maior que 1,97 e a relação Naa/Cr é menor que 1,12, o que torna este método importante no planejamento do tratamento e monitorização da eficácia terapêutica.